2004
DOI: 10.1002/pmic.200400818
|View full text |Cite
|
Sign up to set email alerts
|

Activation and expression of proteins during synchronous germination of aerial spores of Streptomyces granaticolor

Abstract: Synchronously germinating aerial spores of Streptomyces granaticolor were used to study protein activation and expression during the transition from dormant to metabolically active vegetative forms. The first phase of protein activation is associated with the solubility of proteins. Three major chaperones, DnaK, Trigger factor, and GroEL, were identified in spores. Enhancement in rate of protein synthesis during germination was accompanied by the association of TF and DnaK with ribosomes. During germination, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 44 publications
4
38
4
Order By: Relevance
“…Phosphorylation of enolase, trigger factor, triose isomerase, fructose biphosphate aldolase, glyoxalase, pyruvate dehydrogenase, and phosphate acetyl transferase could be identified in this report (Lomas-Lopez et al, 2007). Counterparts of some of these phosphorylated proteins have been previously described as substrates of Ser/Thrspecific phosphorylation in other bacteria, such as fructose-1,6-biphosphate aldolase in Streptococcus pneumoniae (Novakova et al, 2005) and Corynebacterium glutamicum (Bendt et al, 2003), trigger factor in Bacillus subtilis (Levine et al, 2006) and Streptomyces granaticolor (Bobek et al, 2004), elongation factor P in C. glutamicum (Bendt et al, 2003) und S. granaticolor (Bobek et al, 2004) and enolase in B. subtilis and C. glutamicum (Bendt et al, 2003). The results of all these studies underscore the important regulatory function of STKs in central metabolic pathways in bacteria.…”
Section: Substrates Of Pknbmentioning
confidence: 73%
“…Phosphorylation of enolase, trigger factor, triose isomerase, fructose biphosphate aldolase, glyoxalase, pyruvate dehydrogenase, and phosphate acetyl transferase could be identified in this report (Lomas-Lopez et al, 2007). Counterparts of some of these phosphorylated proteins have been previously described as substrates of Ser/Thrspecific phosphorylation in other bacteria, such as fructose-1,6-biphosphate aldolase in Streptococcus pneumoniae (Novakova et al, 2005) and Corynebacterium glutamicum (Bendt et al, 2003), trigger factor in Bacillus subtilis (Levine et al, 2006) and Streptomyces granaticolor (Bobek et al, 2004), elongation factor P in C. glutamicum (Bendt et al, 2003) und S. granaticolor (Bobek et al, 2004) and enolase in B. subtilis and C. glutamicum (Bendt et al, 2003). The results of all these studies underscore the important regulatory function of STKs in central metabolic pathways in bacteria.…”
Section: Substrates Of Pknbmentioning
confidence: 73%
“…Streptomyces biology has been studied using proteomics approaches in various cellular contexts, including programmed cell death (8), germination (17,18), mutant analysis (bald A mutant) (19 -21), phosphate limitation (22), and the diauxic lag phase (23). Most of these experiments only gave qualitative information, using mainly two-dimensional gel electrophoresis for protein separation followed by mass spectrometry for protein identification.…”
mentioning
confidence: 99%
“…The possible role of chaperones in germination was discussed in the work of Bobek et al [8]. There were also significantly more genes that were involved in the translational machinery (the elongation factors, RNA polymerase subunits), the energy metabolism and, strikingly, the cold shock genes.…”
Section: Resultsmentioning
confidence: 99%
“…Cell wall hydrolases, such as RpfA and SwlA, provide the lysis of spore peptidoglycan to allow the entrance of external nutrients [7]. The re-activated chaperones GroEL, Trigger factor and DnaK were detected as assisting the reactivation of the proteosynthetic apparatus, which is fully accelerated during the first initial steps [8]. A systematic proteomic study that was recently conducted on streptomycete spore germination [3] revealed that the first newly expressed proteins are members of proteosynthetic machinery, proteins that are involved in differentiation, protein modifiers and other chaperones.…”
Section: Introductionmentioning
confidence: 99%